Influence of supplemental protein concentration on intake, utilization, and quality of diet selected by steers grazing dormant tallgrass-prairie - DelCurto, T.; Cochran, R.C.; Corah, L.R.; Beharka, A.A.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fifteen ruminally and 12 esophageally cannulated steers were randomly assigned to receive low (LP), moderate (MP), and high (HP) crude protein (CP) supplements in a 23-day winter grazing trial designed to evaluate dormant tallgrass forage intake and utilization. Supplemental CP levels were 13, 26, or 39%, respectively. Forage organic matter (OM) intake was greatest (P<.05) for the MP steers. Likewise, fiber (NDF) digestibility and ruminal fill were largest (P<.10) for the MP treatment. Furthermore, the quality of diet selected tended to improve with increasing supplemental protein concentration. Increasing CP concentration in supplements dramatically improves the intake and utilization of dormant forage. In this study, intake and digestibility were optimized with the MP supplement.
Keywords: Beef; Protein concentrations; Intake; Utilization; Quality; Steers; Dormant tallgrass-prairie